Interference logic elements based on a Y-shaped defect photonic crystal - P.V. Mokshin; D.L. Golovashkin; V.S. Pavelyev (Компьютерная оптика)
Abstract: We discuss prospects of using a photonic crystal with a Y-shaped defect for the implementation of interference logic elements. By the numerical modeling we demonstrate that such photonic-crystal elements can implement logic operations such as "AND", "OR", "XOR" and "NOR". Particular attention is given to demonstrating the possibility of cascading such elements with the aim of synthesizing composite interference logic elements capable of implementing other logic operations.